FRI0299 Prevalence of Vertebral Fractures in Osteoporotic HIP Fractured Patients: The Focus Study. (9th June 2015) - Arioli, G.; Falaschi, P.; Letizia Mauro, G.; Iolascon, G.; Invernizzi, M.; Noale, M.; Manfredini, M.; Bernardi, G.; Cisari, C.
Abstract : Background: Osteoporosis is a multifactorial systemic skeletal disease, characterized by low bone mass and microarchitectural modifications of bone tissue, with a consequent increase in fragility fractures [1]. Vertebral fractures are the most prevalent osteoporotic fractures and osteoporotic hip fractures are the most serious complication of osteoporosis resulting in increased mortality and high socio-economic cost [2, 3]. The coexistence of these two pathological conditions in elderly patients has been previously described, leading to even worse functional outcomes than each one alone [4]. Objectives: To determine the prevalence of vertebral fractures in osteoporotic hip fractured women and to evaluate the relationship between prevalence of vertebral fractures and pre-existing factors such us autonomy in daily life activity, quality of walking, numbers of falls, cognitive aspects and comorbidities. Methods: 946 osteoporotic hip fractured women aged more than 60 years and with an X-ray evaluation of spine were consecutively enrolled in 25 Orthopaedic, Physical Medicine and geriatric centers in Italy. After spine X-ray morphometry patients were divided in two groups: previous vertebral fracture (F) and no previous fracture (NF). Moreover anamnestic, demographical and outcome related data (ADL, IADL, CIRS, SPMSQ, FAC and RANKIN scale) were collected. Results: Prevalent vertebral fractures were present in 502 (54%) patients. 119 (13.7%) patients had at least one severe fracture. The F compared to NF group showed statistically significant worse scores regarding the pre hip fracture values of RANKIN, CIRS, SPMSQ, IADL and the overall number of falls (p<0.001). Moreover the F group showed statistically significant lower values of serif 25(OH)D than NF group (p<.0.001). Conclusions: Previous Vertebral fractures in hip fractured patients are a common issue and negatively influence several functional and cognitive outcome measures in these patients. References: NIH Consensus Development Panel on Osteoporosis Prevention, Diagnosis and Therapy. Osteoporosis prevention, diagnosis and therapy. JAMA. 2001;285:785–795 Sattui SE, Saag KG. Fracture mortality: associations with epidemiology and osteoporosis treatment. Nat Rev Endocrinol. 2014 Oct;10(10):592-602. Svedbom A, Hernlund E, Ivergård M, Compston J, Cooper C, Stenmark J, McCloskey EV, Jönsson B, Kanis JA; EU Review Panel of IOF. Osteoporosis in the European Union: a compendium of country-specific reports. Arch Osteoporos. 2013;8(1-2):137. Gonnelli S, Caffarelli C, Maggi S et al. The assessment of vertebral fractures in elderly women with recent hip fractures: the BREAK Study. Osteoporosis In.t 2013;24:1151-1159 Disclosure of Interest: None declared